Enkapsulasi Probiotik Lactobacillus sp. Menggunakan Biopolimer Alginat dan Kitosan dengan Metode Satu Tahap - Tazkia Nur Hidayah; Djaenudin Djaenudin; Novriyanti Lubis (Jurnal Serambi Engineering, 2021)
Lactobacillus sp are gram-positive bacteria that cannot survive in acidic conditions, such as stomach acid conditions (pH 1.5- pH 2.5) so that a carrier is needed so that Lactobacillus sp can survive when colonizing the intestine. One way to protect Lactobacillus sp in acidic conditions is by encapsulation. The core material used for Lactobacillus encapsulation uses a mixture of Na-alginate and chitosan. The mixture formed then becomes microcapsules using an electrospinning device. One of the components of the electrospinning device is a syringe that provides pressure to form droplets that fall into a solution of CaCl2 and chitosan with a concentration of 1.2%; 1.6% and 2%. Lactobacillus sp. The encapsulated viability was tested for viability in simulated gastric acid (0.2% NaCl pH 1.2 and pH 3) for 1 minute, 60 minutes, and 120 minutes using the Total Plate Count (TPC) method. After the viability test was carried out, it was found that Lactobacillus sp. encapsulation results with a 2% chitosan matrix with the number of colonies in the simulated gastric acid pH 3 for 1 minute is 4x109 cfu / g, for 60 minutes 3x109 cfu / g and for 120 minutes is 1x9 cfu /g.